Informal learning: The experience of adult educators at work - John Garrick; Paul Hager (Adult Education Research Conference, 1996)
This paper examines the term informal learning. It uses an interpretive research methodology to study how individual adult educators learn at work, personal factors which influence this, and the effects of the micro-politics of complex organizations upon informal learning. The paper concludes that there is a need for a broader conception of informal learning.